EXPERIMENTAL CLASSES WITH AN ANDRAGOGY APPROACH TO MAKE THE LEARNING ATMOSPHERE FUN AND VIBRANT (CASE STUDY AT THE BSSN TRAINING CENTER) - Setyowati, Anik; Tyahadi, Agas (PEOPLE: International Journal of Social Sciences, 2019)
Andragogy as an adult learning need a lot of innovation to maintain "transfer of knowledge" process with a comfortable atmosphere in the classroom. Prequisite knowledge as matriculation need to be learned first before class start, then they will comfy to interact on the learning process. take a long learning hour with aged participant can causes physical problems and it will affect on the achievement of learning goals, this effect continue to double with boredom and low motivation and the result was demotivation and uncomfortable class atmosphere. In this paper wrier take observations of training participant and conducts experimental classes as a teacher to find the best method to overcome the problems mentioned before. Taking observation on 3 examples of role model instructors with different, unique and efficient learning methods. Calibrate the result with interviews of fellow instructors and direct question on training participants. Then the results of observations, experiments and interviews were compared with literature studies. Conclution to this studies is combining 2 or more teaching methods in teaching action produced a pleasant classroom atmosphere and made the training participants enthusiastic in achieving maximum learning outcomes, and define the relation of the learning method, the learning material, Participants Chraacter and Time of implementation.